Geogebra: uma ferramenta dinâmica na aprendizagem da Geometria no Ensino Básico - DINIZ, Joel Felix Silva (2016)
This work proposes the rescue of the teaching of geometric constructions in Basic Education in a way diferent from traditional ones. Here is made use of new technologies, in particular GeoGebra free software is used instead of the static form of ruler and compass, especially in the development of concepts, properties and theorems of geometry, fundamental for understanding the steps of construction. It is also made a detailed survey of the contributions that ICTs propose for the improvement of mathematics teaching, as well as their contributions from PCNs that encourage the use of ICTs. A detailed study of GeoGebra software for Smartphones is done, to better develop this work in the classroom. The methodology used was experimental research, where a study was carried out with the software GeoGebra in version 5.0 and also in the version Grapher 3D, being applied in classes of 7 and 9 years of Elementary School and in a group of the 3rd year of High School .